The use of bentonite and zeolite as caesium-binders in feed to reindeer - experiences from Sweden - Birgitta Åhman (Rangifer, 1990)
Feeding is used in Sweden to lower radiocaesium levels in reindeer before slaughter. In feeds used for this purpose, bentonite is added as a caesium-binder to prevent absorption of radiocaesium, since the animals usually have som access to contaminated pasture in their corrals. Bentonite is efficient as a caesium-binder but increases water consumption and excretion of urine. Zeolite has been used as a caesium-binder to reindeer in a few experiments. The effect, however, has been inferior to that of bentonite. It seems that zeolite, mixed in feeds, loose some of its effect as the feed is stored. The need of a caesium-binder is demonstrated by results from practical feeding of reindeer where radiocaesium levels have not decreased as expected when feed without bentonite has been used.